Effect of Posterior Malleolus Fracture on Syndesmotic Reduction: A Cadaveric Study. (7th February 2018) - Fitzpatrick, Elizabeth; Goetz, Jessica E.; Sittapairoj, Tinnart; Hosuru Siddappa, Vinay; Femino, John E.; Phisitkul, Phinit
Abstract : Background: Syndesmotic malreduction and fractures of the posterior malleolus negatively influence outcomes of rotational ankle fractures. Recent data have shown that posterior malleolus fixation contributes to the stability of the syndesmosis. The purpose of this study was to analyze syndesmotic reduction within the context of different sizes of posterior malleolus fracture fragments and different qualities of reduction. Methods: A model of stage-IV supination-external rotation injury was created in 9 through-the-knee cadaveric specimens. The specimens were randomized to receive either a small (one-third of the incisura, n = 4) or a large (two-thirds of the incisura, n = 5) posterior malleolus fracture. High-resolution computed tomography (CT) scans were obtained of each intact specimen and then with clamp reduction of the syndesmosis along with a fracture fragment that was (1) unreduced, (2) anatomically reduced, or (3) fixed with a 4.8-mm-gap malreduction. Syndesmotic reduction in both the anterior-posterior and the medial-lateral direction was assessed relative to the intact specimen. Results: Clamp reduction of the syndesmosis increased medial translation of the distal part of the fibula in the specimens with an unfixed or an anatomically fixed posterior malleolus fracture fragment and caused lateral displacement of the distal part of the fibula in the specimens with gap malreduction of the posterior malleolus fracture. Clamp reduction of the syndesmosis caused a slight anterior shift of the fibula in the specimens with a small unfixed or anatomically fixed posterior malleolus fracture fragment and caused a posterior shift of the fibula in the specimens with gap malreduction of a large fragment. Conclusions: The overall anterior-posterior reduction of the syndesmosis was generally unaffected by a posterior malleolus fracture except when there was malreduction of a large fragment. Medial-lateral syndesmotic reduction was affected by the conditions of the posterior malleolus fixation, with malreduction of the posterior malleolus leading to syndesmotic malreduction. Clinical Relevance: When posterior malleolus fractures occur with syndesmotic injury, anatomic fracture reduction and fixation are paramount as they can affect syndesmotic reduction, especially with larger fragments.